Reconstruction of Discipline in Parenting Students between Ta'dib and a Sense of Security: A Critical Review of Islamic Boarding School Literature in the Context of Child-Friendly Islamic Boarding Schools: Rekonstruksi Disiplin Pengasuhan Santri antara Ta’dib dan Rasa Aman: Telaah Kritis Literatur Pesantren dalam Konteks Pesantren Ramah Anak - Abdul Wasik; Fadhila Sidiq Permana; Inayatur Robbaniyah Karim (Edukasi: Journal of Educational Research, 2026)
This study analyses how discipline is constructed in Ta’lim al-Muta’allim and Washāyā al-Ābā’ li al-Abnā’, and examines the relationship between the paradigm of ta’dib and the sense of safety in the care of santri. The study is important because scholarship on pesantren discipline has largely focused on adab and character formation, whereas studies on child-friendly pesantren have tended to emphasise policy and protection. As a result, dialogue between classical pesantren literature and santri’s sense of safety remains limited. This study employs a qualitative design using library research and critical text analysis. The primary sources are the two classical texts, while the secondary sources consist of books, journal articles, regulations, and relevant reports. Data were collected through documentation and close reading, and analysed using qualitative content analysis and thematic analysis. The findings show that discipline in both texts is conceived as a process of moral formation grounded in intention, character, perseverance, respect for teachers, and self-regulation, rather than merely as punishment. When read through the lens of safety, the paradigm of ta’dib reveals ethical convergences alongside relational tensions and normative gaps. This study argues that reconstructing santri discipline does not require abandoning ta’dib, but reorienting its operational boundaries so that it becomes more ethical, protective, and compatible with child-friendly pesantren. The originality of this study lies in bringing a critical reading of classical pesantren literature into dialogue with santri protection.